Pengaruh konflik, komitmen organisasi dan kepuasan kerja terhadap loyalitas karyawan pada Rumah Sakit TK. III, dr. Reksodiwiryo padang (studi kasus pada seluruh staf non medis) - Sopali, Mardhatila Fitri; Azizi, Putri; Karlinda, Ai Elis (Journal of Information System, Applied, Management, Accounting and Research, 2021)
This study aims to determine how big the influence of Conflict, Organizational Commitment and Job Satisfaction together on Employee Loyalty at Tk Hospital. III dr. Reksodiwiryo Padang. The method of collecting data is through surveys and distributing questionnaires, with a sample of 57 respondents. Non-medical staff at Tk Hospital. III dr. Reksodiwiryo Padang. The analytical method used is multiple regression analysis. The results obtained based on the partial test (t test) obtained: (a) partially there is a significant effect of Conflict on Employee Loyalty. Thus Ha is accepted, Ho is rejected. (b) partially there is a significant effect of Organizational Commitment on Employee Loyalty. Thus obtained Ha accepted Ho rejected. (c) partially there is no significant effect of Job Satisfaction on Performance Loyalty. Thus, Ha is rejected, Ho is accepted. (d) There is a spatially significant influence between Conflict, Organizational Commitment, and Job Satisfaction on Employee Loyalty. Thus obtained Ha accepted Ho rejected. (e) the contribution of the variables of Conflict, Organizational Commitment, and Job Satisfaction together to Employee Loyalty is 40.2% while the remaining 59.8% is influenced by other variables not examined in this study.